2021
DOI: 10.1002/hep4.1786
|View full text |Cite
|
Sign up to set email alerts
|

Risk Prediction of Nosocomial and Posthospital Discharge Infections in Alcohol‐Associated Hepatitis

Abstract: Alcohol-associated hepatitis (AAH) is a severe form of liver injury with mortality as high as 30%-40% at 90 days. As a result of altered immune function in AAH, bacterial infections are common and are associated with poor outcomes. However, determining the risk and subsequent development of infection in patients with AAH remain challenging. We performed a retrospective study of consecutive patients admitted with a diagnosis of AAH at two independent tertiary centers from 1998 to 2018 (test cohort, n = 286) who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In this study, chronic liver disease male patients (130(62.8%)) with mean age of (49.5 ± 11.9) years had significant increase in incidence of NCI. This was in agree with Penrice et al who mentioned that 66% men, and the median age was 48 [20]. On the other hand, Griemsmann et al found no major differences in the incidence and outcome of nosocomial infections between male and female patients [3].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, chronic liver disease male patients (130(62.8%)) with mean age of (49.5 ± 11.9) years had significant increase in incidence of NCI. This was in agree with Penrice et al who mentioned that 66% men, and the median age was 48 [20]. On the other hand, Griemsmann et al found no major differences in the incidence and outcome of nosocomial infections between male and female patients [3].…”
Section: Discussionsupporting
confidence: 89%
“…Patients with AH are at high risk of developing infection, a major cause of mortality in this setting, which is increased by up to 70% with corticosteroid treatment 4,11 . The most common infections are urinary tract infection, bacteremia, lower respiratory tract infection, and spontaneous bacterial peritonitis (SBP) 12–14 . The high incidence of infections is associated with immune dysfunction; increased T‐cell exhaustion leads to reduced ability to prevent bacterial infection 5,10 .…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 11 The most common infections are urinary tract infection, bacteremia, lower respiratory tract infection, and spontaneous bacterial peritonitis (SBP). 12 , 13 , 14 The high incidence of infections is associated with immune dysfunction; increased T‐cell exhaustion leads to reduced ability to prevent bacterial infection. 5 , 10 Despite high circulating levels of pro‐inflammatory cytokines TNF‐α, IL‐8, and IL‐17, which are anti‐pathogenic in other conditions, 15 , 16 immune cells are refractory to stimulation by microbial products in patients with AH, suggesting an impaired response to infection.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been reports of organisms responsible for nosocomial infections exhibiting resistance to several medicines, making it harder to treat bacterial infections. In addition, new patients who move into a room previously occupied by a patient with MAR infections are at an increased risk of contracting these pathogens because they are more likely to come into contact with them (Penrice et al 2021).…”
Section: Introductionmentioning
confidence: 99%